2022
DOI: 10.1155/2022/2271788
|View full text |Cite|
|
Sign up to set email alerts
|

NOD1 and NOD2 Are Potential Therapeutic Targets for Cancer Immunotherapy

Abstract: The nucleotide oligomerization domain (NOD)-like receptors (NLRs) are a group of intracellular proteins that are essential for controlling the host's innate immune response. The cytosolic nucleotide binding oligomerization domains 1 and 2 receptors (NOD1 and NOD2) are the most widely investigated NLRs. As pattern recognition receptors (PRRs), NOD1 and NOD2 may recognize and bind endogenous damage associated molecular patterns (DAMPs) and external pathogenic associated molecular patterns (PAMPs), directing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Both HIF-1A and c-MYC were also confirmed to be downregulated upon MIAT silencing in leukemic T cells. The role of HIF-1A in cancer is well reported, and HIF-1A was found to be upregulated in various types of leukemia [ 49 , 50 , 51 , 52 , 53 ]. The upregulation of this gene was also found to activate the NF-κB pathway, and its downregulation led to a decrease in the proliferation and an increase in the inhibition of apoptosis in AML leukemic cell lines [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both HIF-1A and c-MYC were also confirmed to be downregulated upon MIAT silencing in leukemic T cells. The role of HIF-1A in cancer is well reported, and HIF-1A was found to be upregulated in various types of leukemia [ 49 , 50 , 51 , 52 , 53 ]. The upregulation of this gene was also found to activate the NF-κB pathway, and its downregulation led to a decrease in the proliferation and an increase in the inhibition of apoptosis in AML leukemic cell lines [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of HIF-1A in cancer is well reported, and HIF-1A was found to be upregulated in various types of leukemia [ 49 , 50 , 51 , 52 , 53 ]. The upregulation of this gene was also found to activate the NF-κB pathway, and its downregulation led to a decrease in the proliferation and an increase in the inhibition of apoptosis in AML leukemic cell lines [ 49 ]. c-MYC has been extensively associated with oncogenic functions, carcinogenesis, angiogenesis, chemoresistance, and many more cancer-promoting roles [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, NOD1 exerts its anti-tumor effects through the induction of apoptosis, but uncontrolled apoptosis mediated by NOD1 might induce immunosuppression microenvironment, thereby promoting tumor progression. Furthermore, the anti-inflammatory function of NOD2 is dependent on the recognition and binding of bacteria and their derivatives, and when this association is inadequate, NOD2 contributes to chronic inflammation and promotes cancer ( Zhang et al, 2022b ; Wang, 2022 ). Hence, direct targeting NOD1/2 against tumor may result in a therapeutic effect that contradicts expectations.…”
Section: Perspectivementioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%